Influence of construction factors on the vibrational activity of the gearing - Bogusław ŁAZARZ; Grzegorz PERUŃ (Transport Problems, 2012)
The paper presents the results of numerical and experimental studies on the influence of selected factors on the dynamic effects and vibroactivity of the gearing. The studies were performed using a custom developed dynamic model of a test stand with the gears operating in the circulating power system.